PENGARUH CITRA PEMBUAT/CORPORATE IMAGE, CITRA PEMAKAI/USER IMAGE, DAN CITRA PRODUK/PRODUCT IMAGETERHADAPLOYALITAS NASABAH PRODUK TABUNGAN BRITAMAPADA PT. BANK RAKYAT INDONESIA KOTA LHOKSEUMAWE - Zulfikar Zulfikar; Hamdani Hamdani (Ekonis: Jurnal Ekonomi dan Bisnis, 2017)
This study aims to determine the effect of several variables such as corporate’s image variable, the user image variable and the product image variable on customer loyalty of BritAma products at PT BRI Branch of Lhokseumawe either partially or simultaneously. The total sample of this research are as many as 96 people and the method used for the sampling is quota Accidental Sampling. Data analysis in this research will applying both descriptive method in explaining the research data and description and using quantitative methode while analyzingdata using through a multiple linear regression model.  The result shows that regression coefficient of corporatie’s image 0,354 with the value score of 0,027, meanwhile regression coefficient of user’s image is 0,871 with the value score of  0,000 that is lower than 0,05. The third variable which is the product image variable obtains a score of 0,119 with the value score of  0,003 that is also lower than 0,05. These results show that all variables namely corporate’s image, the user image variable and the product image variable havepositive and significant impact on customer loyalty of BritAma products at PT BRI Branch of Lhokseumawe. Moreover, the highest impact variable in building customer loyalty will be the user image variable.  Kata Kunci : Loyalitas, Corporate Image,User Image,Product Image